Tetramethylpyrazine nitrone protects retinal ganglion cells against N‐methyl‐d‐aspartate‐induced excitotoxicity. Issue 3 (3rd March 2017) - Luo, Xiaopeng; Yu, Yankun; Xiang, Zongqin; Wu, Huisu; Ramakrishna, Seeram; Wang, Yuqiang; So, Kwok‐Fai; Zhang, Zaijun; Xu, Ying
Abstract: Adding a free radical‐scavenging nitrone moiety on tetramethylpyrazine, we have previously synthesized a chemical named 2‐[[(1, 1‐dimethylethyl)oxidoimino]‐methyl]‐3, 5, 6‐trimethylpyrazine (tetramethylpyrazine nitrone, or TBN) and proved its neuroprotective effect but with limited understanding of its mechanism. Here we ask if TBN protects retinal ganglion cells (RGCs) against excitotoxicity induced by NMDA and explore the underlying mechanism. NMDA was intravitreally injected to induce RGC injury in rats, followed by daily intraperitoneal administrations of TBN. Measurements of TBN concentration at different times after intraperitoneal administration showed that more than 200 μM TBN reached the aqueous humor quickly. Then RGCs' survival was evaluated by quantifying Brn3‐positive cells, and retinal functions were examined by electroretinogram and visual behaviors. TBN significantly increased the survival of RGCs after NMDA insult, recovered the amplitude of photopic negative responses to flash, and restored the visual behavior. Furthermore, TBN inhibited the apoptotic process, as indicated by the elevated ratios of cleaved caspase‐3/caspase‐3 and of Bax/Bcl‐2, and decreased the level of reactive oxygen species. Moreover, TBN reduced RGC's calcium overload induced by NMDA or by KCl. Whole‐cell patch recording from RGCs further showed that TBN slightly but significantly inhibited L‐type calcium channels, but had little effect on T‐type calcium channel or NMDA‐, α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid(AMPA)‐induced current. Thus our data indicate that TBN alleviates NMDA‐elicited injury of rat RGCs both morphologically and functionally, possibly by inhibiting the L‐type calcium channel thus reducing Ca 2+ overload and by directly scavenging free radicals. Therefore, TBN may be a novel candidate for treating excitotoxicity‐related visual disorders such as glaucoma. Abstract : We previously synthesized TBN and showed a neuroprotective effect but know little about its mechanism. Here we show that TBN alleviates NMDA‐elicited injury of rat retinal ganglion cells (RGCs) both morphologically and functionally, possibly by inhibiting the L‐type calcium channel, thus reducing Ca 2+ overload, and by directly scavenging free radicals. Therefore, TBN may be a novel candidate for treating excitotoxicity‐related visual disorders such as glaucoma.